The effect of utilizing zakat fund on financing production to achieving social welfare: in Indonesia as a case study - Riyadi, Aditya Hadid; Sheik Abdukad, Abdukadir Abdullahi; Mohammed Sai, Bandar; Ahmed Takow, Hawa; Sharofiddin, Ashurov (IIUM Press, 2021)
Indonesia has tremendous potential for the development of Islamic social finance. Besides having the largest number of Muslims in the world, Indonesia is also the most generous country in the world (World Giving Index 2018). However, the reality in the field of management of Islamic social finance, especially Zakat, is still far from expectations. It was projected that in 2018, Indonesia would be able to collect only 28% of the total potential Zakat funds.This situation was compounded by the fact that only 84% of the collected funds were distributed(BAZNAS 2019). One of the reasons was the absence among the Zakatinstitutions of efficient Zakatprograms that are in line with the needs of the community. Therefore, there is an urgent need for synergy between Zakatinstitutions and Islamic microfinance institutions that are experienced in developing SMEs, which are mostly underfunded.This paper will discuss the synergy scheme between Zakatinstitution and Islamic microfinance in maximizing the distribution of productive Zakatto to the public. This paper uses qualitative methods, analyzing references from journals, Zakatinstitutions' reports, and other related literature. From this current research, it is found that the management of productive Zakatfunds in Indonesia is still not unsatisfactory, as evidenced by the low distribution rate of Zakat funds. This paper provides recommendations so that Zakatand Islamic microfinance institutions can work together in the management of productive Zakatthat reaches the targeted poor and alleviates poverty and enhance community welfare.